Penerapan Budaya Positif Parsel Si Margaret SD Negeri Wonorejo - Dewi Nuraeni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Positive Culture is very important to implement in elementary schools, especially at Wonorejo State Elementary School. Through Positive Culture, good habits can grow optimally and consistently. For this reason, it is necessary to implement the Positive Culture